2022
DOI: 10.1186/s13063-022-06390-x
|View full text |Cite
|
Sign up to set email alerts
|

PragmaTic, prospEctive, randomized, controlled, double-blind, mulTi-centre, multinational study on the safety and efficacy of a 6% HydroxYethyl Starch (HES) solution versus an electrolyte solution in trauma patients: study protocol for the TETHYS study

Abstract: Background Trauma may be associated with significant to life-threatening blood loss, which in turn may increase the risk of complications and death, particularly in the absence of adequate treatment. Hydroxyethyl starch (HES) solutions are used for volume therapy to treat hypovolemia due to acute blood loss to maintain or re-establish hemodynamic stability with the ultimate goal to avoid organ hypoperfusion and cardiovascular collapse. The current study compares a 6% HES 130 solution (Volulyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…An ongoing prospective randomized controlled trial (TETHYS; NCT03338218) is likely to inform about the efficacy and safety of 6% HES 130/0.4 in the modern practice of trauma resuscitation. 68…”
Section: Modulators Of Fviii/vwf Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ongoing prospective randomized controlled trial (TETHYS; NCT03338218) is likely to inform about the efficacy and safety of 6% HES 130/0.4 in the modern practice of trauma resuscitation. 68…”
Section: Modulators Of Fviii/vwf Levelsmentioning
confidence: 99%
“…67 An ongoing prospective randomized controlled trial (TETHYS; NCT03338218) is likely to inform about the efficacy and safety of 6% HES 130/0.4 in the modern practice of trauma resuscitation. 68 THERAPEUTIC IMPLICATIONS Low FVIII and VWF are infrequent, and clinical experience of desmopressin mainly focuses on potential reversal of P2Y 12 inhibitors in TBI. There is a paucity of robust data that supports or refutes the role of desmopressin (0.3 µg/kg) in this setting.…”
Section: Hydroxyethyl Starchmentioning
confidence: 99%
“…The outcomes and the investigators’ critical remarks can be found in Table 2 . Two trials (Safety and Efficacy of a 6% Hydroxyethyl Starch Solution vs. an Electrolyte Solution in Trauma Patients (TETHYS); Safety and Efficacy of 6% Hydroxyethyl Starch Solution vs. an Electrolyte Solution in Patients Undergoing Elective Abdominal Surgery (PHOENICS)) are officially registered (NCT03338218, NCT03278548), but no results have been published to date [ 36 , 37 ].…”
Section: Studies Conducted With 6% Hes 130/04 or 042 Analyzing Its Re...mentioning
confidence: 99%
“…However, the lack of significant and consistent benefits in clinical outcomes and the potential for harm make it difficult to justify the use of HES in clinical practice. In this context, the findings of two ongoing surgical trials on 6% HES 130/0.4 (PHOENICS and TETHYS studies) 17 , 18 are urgently needed to add evidence to this controversial discussion.…”
mentioning
confidence: 99%